Oil sparks in the Amazon : local conflicts, indigenous populations, and natural resources - Vasquez, Patricia I. (Athens, Georgia : University of Georgia Press, 2014)
"For decades, studies of oil-related conflicts focused on the causes and effects of natural resources mismanagement, commonly known as the "resource curse"-the paradoxical connection between oil wealth and economic busts (as in Venezuela) or, in a later twist, the link between the predatory behavior of armed rebel organizations and the abundant natural resources that funded their existence. Patricia Vasquez notes that oil busts and civil wars associated with the resource curse were quite different from the now-predominant local hydrocarbons disputes that are multiplying rapidly in Latin America. These more recent, localized disputes-over land, population displacement, water contamination, oil jobs that are promised but never materialize, etc.-primarily involve Indigenous groups with a different social and cultural identity from the rest of the population. Vasquez spent fifteen years making regular field visits to the oil-producing regions of Latin America and conducting hundreds of interviews with the various stakeholders in these local conflicts. Her book, based on this field research, analyzes the dynamics that characterize each of fifty-five social and environmental conflicts related to oil and gas extraction in the Andean countries (Peru, Ecuador, and Columbia). She is interested not in promulgating a new theory of conflict but in examining the triggers of local hydrocarbons disputes and providing policy recommendations to resolve or prevent them"--
Includes bibliographical references and index.
Description based on print version record.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Petroleum industry and trade -- Social aspects -- South America; Petroleum industry and trade -- Environmental aspects -- South America; Indians of South America -- Social conditions; Social conflict -- South America; Electronic books